Benjamin C. Gruenberg and Sidonie Matsner Gruenberg papers - Gruenberg, Benjamin C. (Benjamin Charles), 1875-1965.; Gruenberg, Sidonie Matsner, 1881-1974.
Correspondence, diaries, speeches, writings, notes, newspaper clippings, printed matter, and other papers.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Benjamin C. Gruenberg, author and educator. Sidonie M. Gruenberg, author and child study specialist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.